Biological Perspective Analysis on Education Level and Motivation in the Implementation of Premarital HIV Screening Tests: A Quantitative Study with a Cross-Sectional Design - Tetin Rismayanti; Iip Latipah; Ira Jawahir; Kartini; Indah Novita Sari; Ineu Komala (Postgraduate, University of Mataram, 2024)
The research aims to explore how education level and motivation influence the adoption of premarital HIV screening tests in Pasar Kemis District, Tangerang Regency, in 2024, focusing on biological perspectives of HIV. HIV, a virus impacting human immunity by targeting CD4 cells crucial for immune response, underscores the significance of understanding its biological mechanisms to enhance early detection and prevent transmission. Using a quantitative approach with a cross-sectional design, the study involves 61 mothers of prospective brides and grooms, sampled through accidental selection. Data collection utilizes a questionnaire to gather primary data, analyzed via chi-square tests. Preliminary findings reveal a substantial 63.94% participation rate in premarital HIV screening, with 52.52% having higher education and 63.9% showing high motivation. Bivariate analysis demonstrates a significant correlation between education (p-value = 0.001) and motivation (p-value = 0.000) with the uptake of premarital HIV testing. Emphasizing the role of education and motivation in promoting HIV screening, the study advocates for encouraging prospective couples to undergo testing early. This proactive approach aims to identify and manage potential HIV infections promptly, mitigating further transmission and enhancing overall health outcomes.